Social media and moral decline of Muslim youth in Sabah - Ahmad Tarmizi Abdul Rahman; Nor-Ina Kanyo; Santi Hairuddin; Nurul A’fifah Muarifin Sufianto (Asian Scholars Network, 2022)
Social media is a medium for communication that can connect users around the world easily and quickly. Social media is a popular application used by youth to interact with each other. However, the role is changing when users do not use social media properly and ethically to have a significant impact on the formation of their behaviours and personality. Therefore, this paper discusses the development of social media today that it is able to decrease moral values especially among Muslim youth in Sabah. In general, this study is a descriptive quantitative study, and a questionnaire is used as a research instrument. A random sample was taken of 400 respondents consisting of 287 women and 113 men in Kota Kinabalu, Sabah. The results show that social media can influence youth to the negative values that do not parallel to culture and religion. Therefore, every youth must have a strong religious appreciation to be able to protect themselves from being influenced by negative values.